An Overview of Synthetic Approaches towards 1,2,3-Triazoles - Rohila, Yajat; Sebastian, Sharol; Meenaskhi, Meenaskhi; Gupta, Manoj K. (SynOpen, 2024)
In this Spotlight article, the authors highlight synthetic methods of 1,2,3-triazoles from 2002 to the present.
Keywords: triazoles; organic synthesis; azide; alkyne; 1,3-dipolar cycloaddition